Modeling tourists' pro-environmental behavior: a combination of the value-belief-norm theory and environmental identity theory - He, Yunmeng; Xu, Feifei; Wang, Lijun; Nguyen, Hoaidan (Journal of environmental planning and management, 2024)
Tourists' pro-environmental behavior is critical in achieving sustainable tourism. This article examined the driving mechanism of tourists' pro-environmental behavior based on the Value-Belief-Norm and Environmental Identity theory, and: (1) An integrated model was established in both Chinese and Vietnamese tourists, and passed the multiple-group SEM analysis; (2) Environmental values, awareness of consequences, environmental self-identity, and moral norms were important influencing factors of tourists' pro-environmental behavior: Environmental values were basics, which indirectly affected tourists' behavior through awareness of consequences, environmental self-identity, and moral norms; Moral norms were the most direct factors that stimulate pro-environmental behavior; Environmental self-identity, awareness of consequences, and moral norms were mediating variables, which played intermediary roles between environmental values and pro-environmental behavior; (3) Differences between groups were also identified: There was no significant difference except for "environmental values→awareness of consequences", but there were significant differences in the mean score for "environmental values", "awareness of consequences", "moral norms" and "public transport behavior". Implications are made accordingly.